DEVELOPMENT OF SOIL TOTAL NITROGEN DETECTOR USING NEAR-INFRARED LED - Hari Wibowo, Nugroho
Agriculture is one of the important sectors for a country as large as Indonesia with a population of 267 million (2019). Increasing the population causes food needs to continue to increase. One way to meet food needs is to increase the productivity of agriculture. Indonesia as an agrarian country still relies on the traditional system in its farming processes, one of which is plant fertilization. Nitrogen is one of the elements needed by plants, both in the generative and vegetative phases. For plants, nitrogen plays a role in the formation of plant cells, plant tissues and organs. Nitrogen is an element of protein formation and photosynthesis process. The need for the provision of nitrogen is the right dose is very necessary because in addition to optimizing plant growth can also reduce operational costs. Now farmers use more experience to determine how much nitrogen fertilizer must be added. Some farmers conduct tests in the soil laboratory to find out how much total nitrogen is present in the soil, but to do this test farmers have to pay up to Rp 300,000 / test sample and test time around 3 to 4 weeks. The method that can be used to determine the content of a substance is spectroscopy. This method utilizes the interaction that occurs between matter and electromagnetic waves. Near infrared spectroscopy is one type of spectroscopy that can see molecular bonds, including nitrogen in the soil. Spectroscopy works by firing near infrared waves to specific wavelengths into the soil sample and seeing how the intensity of the reflection is generated. The selected wavelength is the wavelength that corresponds to the vibrational frequency of the bond, when it corresponds, the wavelength emitted will be more absorbed and very little is reflected. In this study used a light source in the form of LEDs that can emit light with a narrow wavelength. The selected LEDs have wavelengths of 940, 1200, 1300, 1450 and 1550 nm. The reflected light produced by the soil is captured by a photodiode which then enters the transimpedance amplifier circuit so that it can be read by a microcontroller. The microcontroller will read the voltage data generated by the photodiode at each wavelength and then will be sent to a computer via bluetooth for storage. The soil used in this study is the lembang soil which belongs to the clay soil group with the composition of sand 34.8%, dust 49.73% and clay 15.45%. Prototype testing is divided into two parts, namely an initial test to know the effect of water in the soil and a advanced test to know the total nitrogen content in the soil. In the initial test, 200 grams of each soil sample was dried in the sun for two days then sieved using a mesh measuring 26. Furthermore, the soil samples were added with water 10, 20, 30, 40, and 50 ml of water. In the advanced test, 200 grams of each soil sample was dried under the sun for two days and then sieved using a mesh measuring 26. Furthermore, two grams of urea fertilizer was added to a maximum of 30 grams which had been dissolved in water as much as 50 ml. Reflectance data is taken from each test to see the response. Besides that, in each test the voltage data from soil capacitive sensor and the soil resistive sensor are taken to see the response. At the initial test, it was found that the more water added, the lower the reflectance produced. The greatest reduction in reflectance was found in the amount of 64.36% between dry soil and 50 ml of water added soil. The soil capacitive sensor shows a linear response when water is added to the soil with an R2 = 0.9768, while the soil resistive sensor also shows a linear change but with a lower R2 = 0.9112. In advanced test, it was found that the reflectance graph produced has a different pattern from the reflectance graph produced in the initial test for adding water. On the addition of nitrogen, the resulting reflectance graph has a deeper basin at a wavelength of 1200 to 1550 nm while at a wavelength of 940 nm there is no significant difference. If a regression is performed at each wavelength reflection of the nitrogen content in the soil it is found that at a wavelength of 1300 nm it has the smallest error of 12.047%. The soil capacitance sensor can read the water content quite well, but the resistance sensor cannot read the addition of urea fertilizer solution into the soil. The problem found in this research is the reflectance produced by the soil is diffuse reflectance due to non-uniform surface and scattering effect in the soil. In addition, the initial content in the soil is also unknown, so no other material interacts with the emitted near-infrared waves.